Relation between the Friction Coefficient and Re Number for Spherical Capsule Train-Water Flow in Horizontal Pipes - Ulusarslan, D.; Teke, I. (TAYLOR & FRANCIS INC, 2009)
This experimental study investigated flow regimes of a spherical capsule train-water flow in horizontal pipes. The density of spherical capsules (made of polypropylene, s=0.87) is close to that of ice (s=0.82). The Re number of transition from laminar to turbulent flow for single-phase water in straight pipes is approximately 2300; the experiments indicate that the Re number of transition from laminar to turbulent flow for the two-phase flow of the spherical capsule-water is around 25000. The reduced Re number that explains the capsule concentration effect on transition Re number was defined. New correlations of the friction coefficient were formed based on Rered.. The new correlations for the three flow zones are: laminar zone, [image omitted]; transition zone, [image omitted]; and turbulence zone, [image omitted]. Friction factor correlations were used for calculating the pressure gradient (in the Darcy-Weisbach equation) for hydraulically smooth pipes (with an average deviation of 6.56%).
Keywords: friction coefficient; Moody diagram; pipeline; reduced Re number; spherical capsule train; PIPELINE FLOW; SINGLE CYLINDRICAL; TRANSPORT; OIL; Engineering